Early Baby Bathing Practice and its Associated Factors Among Mothers who Give Birth in the Past One Month in Gurage Zone, Ethiopia, 2022 - Aberash Beyene Derribow MSc; Mebratu Demissie MSc; Seboka Abebe MSc; Megertu Obsa MSc; Fikremariam Endeshaw MSc; Haregwa Asnake MSc; Yirgalem Yosef MSc; Betelhem Taddese MSc (SAGE Publishing, 2023)
Background Ethiopia has still suffered the highest burden of neonatal morbidity and mortality. The World Health Organization's practical guide for the thermal protection of newborns recommends delaying the bathing of newborns for at least 24 h following delivery, as it is crucial to prevent neonatal mortality and morbidity and to achieve 2030 sustainable development goals. However, little is known about delayed newborn bathing practices in Ethiopia. Therefore, the purpose of this study was to assess early baby bathing practices and associated factors among postpartum women. Methods A mixed community-based cross-sectional study was conducted among a total of 582 postnatal mothers. A multistage sampling technique was used to select study participants. A pre-tested and structured questionnaire was used to collect data. The data was entered into Epi-Data version 4.2.0 and exported into SPSS version 23 for analysis. Three focus group discussions with postnatal mothers were used for qualitative data. A purposive sampling method was used. Thematic analysis was used for qualitative data. Bivariate and multivariate logistic regression analyses were used in the analysis. To declare statistically significant, p -values of .05 were used. Result This study revealed that 250 (43%) mothers were practicing early newborn bathing. Early baby bathing was associated with antenatal care (ANC) follow-up (AOR  =  5.1  =  .95% CI  =  (2.6-9.9)), having no recent complications during birth (AOR  =  1.9  =  95% CI  =  (1.02-3.6), having information about the time of baby bathing (AOR  =  6.02, 95% CI  =  (3.9, 9.3)), knowledge of hypothermia (AOR  =  3.3  =  95.6% CI (1.9-5.8), and poor knowledge about neonatal danger signs. Conclusion and Recommendation ANC follow-up, recent complications during birth, having information, knowledge about hypothermia, and neonatal danger signs were significantly associated with early baby bathing. Continuous health education on the appropriate time of baby bathing and neonatal danger signs and enhanced ANC service utilization are recommended.